Modification of Ti‐doped Hematite Photoanode with Quasi‐molecular Cocatalyst: A Comparison of Improvement Mechanism Between Non‐noble and Noble Metals. Issue 10 (22nd April 2021) - Wang, Ruiling; Kuwahara, Yasutaka; Mori, Kohsuke; Qian, Xufang; Zhao, Yixin; Yamashita, Hiromi
Abstract: Loading of molecular catalyst on the surface of semiconductors is an attractive way to boost the water oxidation activity. As active sites, molecular water oxidation cocatalysts show increasing attraction and application possibility. In order to compare the advantages between molecular catalysts with non‐noble and noble metals, the loading of the Fe(salen) and Ru(salen) as cocatalyst precursors on the surface of Ti−Fe2 O3 was investigated Quasi‐Fe(salen) and Ru(salen) improved the photocurrent density by 1.5 and 1.7 times compared to that of the original Ti−Fe2 O3 photoanode, respectively. The quasi‐Fe(salen) could improve the conductivity and reaction kinetics on the photoanode surface. By contrast, the notable advancements could be attributed to more reaction sites for quasi‐Ru(salen) as cocatalysts. Thus, non‐noble quasi‐Fe(salen) is a promising cocatalyst to replace the noble metal salen, and further optimization can be expected with regard to the precise control of reaction sites. Abstract : Iron or ruthenium? Fe(salen) and Ru(salen) are loaded on the surface of Ti−Fe2 O3 nanorods, respectively. After calcination, the quasi‐Fe(salen) and Ru(salen) as cocatalysts are effective for water oxidation reaction, improving the photocurrent density by 1.5 and 1.7 times compared to that of the original Ti−Fe2 O3 photoanode.